Reform in Legal Education: The Nature of Analysis and Results - Sabina, Javdatova (European Journal of Life Safety and Stability (2660-9630), 2021)
This article provides a detailed analysis of the development of the national legal education system in the context of the conceptual reforms implemented in recent years at the Tashkent State Law University.